Real-Time Cost Control in State-Owned Construction Enterprises: Deconstructing Control Latency through the Integration of Internal Audit and AIS - Nurlillah Dwinda Wicaksono; Masiyah Kholmi; Ahmad Juanda (Arkus, 2025)
State-owned enterprises (SOEs) operating within the construction sector face a unique and precarious ecosystem characterized by high financial complexity, intense public accountability pressures, and significant exposure to chronic cost overrun risks. While internal audit (IA) and accounting information systems (AIS) function as established control mechanisms within these entities, they frequently operate in bureaucratic isolation—IA serving as a retrospective compliance function and AIS acting as a passive transaction repository. This functional disconnection creates a critical control latency gap where financial deviations materialize, compound, and metastasize before detection. This study employed a single holistic case study design grounded in a sociotechnical systems paradigm to explore the integration of IA and AIS at PT MM, a subsidiary of a prominent Indonesian construction SOE. Data were collected over a six-month period through eighteen in-depth semi-structured interviews, extensive participatory observation of audit cycles, and comprehensive documentation analysis. Thematic analysis was rigorously applied to deconstruct the socio-technical dynamics of integration. The investigation revealed that prior to integration, IA functions were hindered by a compliance trap, detecting financial anomalies only after 80-90% of project completion. The strategic integration of real-time AIS data into audit workflows transformed the IA function from a policing role to a strategic digital assurance partner. Specifically, a pilot integration in the dock maintenance 2024 project enabled continuous variance analysis, resulting in an 8% reduction in total project costs through the early detection of material price deviations. In conclusion, the synergy between risk-based internal audit (RBIA) and AIS transforms financial control from reactive verification to proactive mitigation. Success depends not merely on technical connectivity but on a cultural shift towards collaborative governance, positioning digital assurance as a critical driver of resilience.